2009
DOI: 10.1002/chem.200801653
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Supramolecular Confinement of Luminol and Heme Proteins to Enhance the Chemiluminescent Quantum Yield

Abstract: Artificial biolumiscence: The use of a supramolecular hydrogel to confine heme proteins and luminol can enhance the quantum yield of chemiluminescence (CL) by about an order of magnitude and give an emission time 4-6 times longer.Confining heme proteins and luminol with the nanofibers of self-assembled molecules was shown to enhance the quantum yield of their chemiluminescence by about an order of magnitude. Supramolecular hydrogels formed using (9-fluorenylmethyl)carbamate (Fmoc) peptides mimicked the cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Chemiluminescence (CL) is the phenomenon when vibronically excited product of an exoergic reaction relaxes back to its ground state with emission of photons [1,2 ]. This analytical method has received considerable attention from many researches over recent decades as a result of its scientific and technological importance to clinical tests and trace detection because of its high sensitivity, wide linear detection range, simple equipment, availability, wide range of applications and inexpensive cost [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemiluminescence (CL) is the phenomenon when vibronically excited product of an exoergic reaction relaxes back to its ground state with emission of photons [1,2 ]. This analytical method has received considerable attention from many researches over recent decades as a result of its scientific and technological importance to clinical tests and trace detection because of its high sensitivity, wide linear detection range, simple equipment, availability, wide range of applications and inexpensive cost [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…This analytical method has received considerable attention from many researches over recent decades as a result of its scientific and technological importance to clinical tests and trace detection because of its high sensitivity, wide linear detection range, simple equipment, availability, wide range of applications and inexpensive cost [1][2][3][4]. Luminol is one of the earliest and most common CL reagents used in CL reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the supramolecular hydrogel formed by the mixture of Fmoc peptides ( 71 + 75 ) is able to mimic the cellular environment of bioluminescence, which improves the quantum yield of chemiluminescence by about an order of magnitude. This simple chemiluminescent system can detect trace levels of blood with 4–6 times enhancement of intensity and better sensitivity for highly diluted samples (Figure 19 B),129 which indicates that this approach could be extended to other applications of chemiluminescent analysis. Moreover, Xu et al.…”
Section: Supramolecular Hydrogels Made Of Amino Acidsmentioning
confidence: 98%
“…Specifically, the supramolecular hydrogel formed by the mixture of Fmoc peptides ( 71 + 75 ) is able to mimic the cellular environment of bioluminescence, which improves the quantum yield of chemiluminescence by about an order of magnitude. This simple chemiluminescent system can detect trace levels of blood with 4–6 times enhancement of intensity and better sensitivity for the highly diluted samples (Figure 19B), [129] indicating that this approach might be extended to other applications of chemiluminescent analysis. Moreover, Xu et al demonstrated that nanofibers in supramolecular hydrogels ( 71 + 75 ) could function as the skeleton of the artificial enzyme and serve as the immobilizing carrier to enhance the catalytic activity of hemin chloride for peroxidation in water or in organic media.…”
Section: Supramolecular Hydrogels Made Of Aminoacidsmentioning
confidence: 99%